Non-communicable diseases related multimorbidity, catastrophic health expenditure, and associated factors in Ernakulam district - Joy, Sarah; Sreedevi, Aswathy; Bhaskaran, Renjitha (Frontiers in Public Health, 2024)
BackgroundMultimorbidity, the coexistence of two or more chronic conditions in an individual, has emerged as a significant public health challenge with profound economic implications, exerting substantial strain on healthcare systems and economies worldwide. This study aimed to estimate the prevalence of non-communicable diseases (NCD) related multimorbidity, catastrophic health expenditure (CHE), and associated factors among adults aged ≥40 years in Ernakulam district.MethodsA community-based cross-sectional study was conducted among 420 individuals aged ≥40 years using population probability sampling. The tools used were the Multimorbidity Assessment Questionnaire for Primary Care (MAQ-PC), the WHO STEPS Questionnaire, and the Patient Health Questionnaire-9 (PHQ-9), which assessed non-communicable diseases, diet, physical activity, smoking, alcohol consumption, and depression. A pretested semi-structured questionnaire collected data on health and household expenditures. Multimorbidity was defined as having two or more self-reported NCDs, and CHE was identified when health costs exceeded 10% of a household’s expenditure in the past month. Multivariable logistic regression was performed to find independent predictors of multimorbidity and CHE.ResultsThe mean age of participants was 60.02 ± 10 years. The prevalence of NCD multimorbidity was 42.6% (95% CI: 37.9–47.3%). The most common dyad was diabetes and hypertension (24.5, 95% CI: 20.4–28.6%). Higher odds of multimorbidity were observed in those aged ≥60 years (aOR = 3.03, 95% CI: 1.95–4.73), unmarried/widowed/divorced (aOR = 2.15, 95% CI: 1.28–3.63), unemployed (aOR = 1.81, 95% CI: 1.14–2.87), and tobacco users (aOR = 3.72, 95% CI: 1.85–7.48). Approximately 32.4% (95% CI: 25.5–39.3%) of households incurred catastrophic health expenditure (CHE) by treating adults with multimorbidity. Age ≥ 60 (aOR = 2.39, 95% CI: 1.99–5.77) and use of outpatient services (aOR = 4.09, 95% CI: 2.01–8.32) were independently associated with higher odds of CHE. IP services and each additional morbidity add ₹22,082.37 (β = 0.557, p < 0.001, 95% CI: ₹17,139.88– ₹27,024.86) and ₹1,278.75 (β = 0.128, p = 0.044, 95%CI: ₹35.58–₹2,521.92) to healthcare costs, respectively.ConclusionThe high prevalence of multimorbidity and associated CHE among individuals over 60 years highlights the urgent need for the National Programme for the Prevention and Control of Non-Communicable Diseases to prioritise multimorbidity and its management, especially above 60 years within this age group.